Increased Expressions of Matrix Metalloproteinases (MMPs) in Prostate Cancer Tissues of Men with Type 2 Diabetes - Franko, Andras (Biomedicines, 2020)
Type 2 diabetes (T2D) is associated with worse prognosis of prostate cancer (PCa). The molecular mechanisms behind this association are still not fully understood. The aim of this study was to identify key factors, which contribute to the more aggressive PCa phenotype in patients with concurrent T2D. Therefore, we investigated benign and PCa tissue of PCa patients with and without diabetes using real time qPCR. Compared to patients without diabetes, patients with T2D showed a decreased E-cadherin/N-cadherin (CDH1/CDH2) ratio in prostate tissue, indicating a switch of epithelial-mesenchymal transition (EMT), which is a pivotal process in carcinogenesis. In addition, the gene expression levels of matrix metalloproteinases (MMPs) and CC chemokine ligands (CCLs) were higher in prostate samples of T2D patients. Next, prostate adenocarcinoma PC3 cells were treated with increasing glucose concentrations to replicate hyperglycemia in vitro. In these cells, high glucose induced expressions of MMPs and CCLs, which showed significant positive associations with the proliferation marker proliferating cell nuclear antigen (PCNA). These results indicate that in prostate tissue of men with T2D, hyperglycemia may induce EMT, increase MMP and CCL gene expressions, which in turn activate invasion and inflammatory processes accelerating the progression of PCa.